Students' Chemistry Multiple Representation Ability in Voltaic Cell Materials - Dea Santika Rahayu; Meili Yanti; Ayu Lestari (Journal of Tropical Chemistry Research and Education, 2023)
Multiple representation ability is a student's understanding of describing a concept at three chemical representation levels: macroscopic, submicroscopic, and symbolic. This ability represents a complete understanding of chemistry, so every teacher needs to know. This research was conducted to analyze students' multiple representation abilities in voltaic cell material using the Predict-Observe-Explain (POE) diagnostic test. This study uses a qualitative descriptive method to obtain an overview of the ability of multiple representations naturally. The instrument uses the POE diagnostic test, has been validated by five validators consisting of lecturers and chemistry teachers and has been tested to obtain instrument legibility. The research subjects involved 34 class XII high school students who had studied voltaic cell material. The findings of the ability profile of multiple representations include (1) the concept of voltaic cell construction; most students (32.35%) are able to understand the constructs at the macroscopic and symbolic levels accompanied by explanations at the submicroscopic level that are not correct, (2) the concept of calculating values standard cell potential, as many as 44.12% of students were able to observe (macroscopic) and calculate (symbolic) the standard cell potential value accompanied by an inaccurate submicroscopic level explanation, (3) most students (32.35%) were not correct in explaining cell voltaic in alkaline batteries at the macroscopic and submicroscopic levels accompanied by writing at the appropriate symbolic level, and (4) the concept of corrosion, most students (35.29%) were able to explain corrosion phenomena at the macroscopic and symbolic levels accompanied by explanations at the submicroscopic level which less correct.